The Natural Syntax of Local Coreference - O'Grady, William (Frontiers in Psychology, 2021)
Emergentist approaches to language are burdened with two responsibilities in contemporary cognitive science. On the one hand, they must offer a different and better understanding of the well-known phenomena that appear to support traditional formal approaches to language. On the other hand, they must extend the search for alternative explanations beyond the familiar languages of Europe and East Asia. I pursue this joint endeavor here by outlining an emergentist account for constraints on anaphora in English and Balinese, with a view to showing that, despite numerous proposals to the contrary, the two languages manifest essentially the same system of coreference and that the system in question is shaped by processing pressures rather than grammatical principles.